Pain Experiences in Individuals with Reported and Suspected Sleep Disorders. Issue 4 (2nd October 2022) - Ravyts, Scott G.; Dzierzewski, Joseph M.
Abstract: The purpose of the present study was to examine whether individuals with varying reported and/or suspected insomnia and sleep apnea presentations differed with respect to pain. Data included 3, 161 adults who participated in an online study investigating sleep and health. Participants reported a lifetime history of prior sleep disorder diagnoses while the presence of suspected sleep disorders was determined using the Insomnia Severity Index and the STOP-Bang. Average pain intensity was assessed using a visual analogue scale and pain interference was determined using two items from the PHQ-15. Participants who reported diagnoses of insomnia and/or sleep apnea reported greater pain intensity and interference compared to those with no sleep disorder; however, no differences in pain were observed between the various reported sleep disorders. Of participants who did not report either insomnia or sleep apnea diagnoses, 24% were suspected of having either insomnia, sleep apnea, or both disorders based on responses to questionnaires. Participants with one or more suspected sleep disorders reported higher pain intensity and interference than those without a suspected disorder. Additionally, having either suspected insomnia or suspected comorbid insomnia and sleep apnea was associated with greater pain intensity compared to only having suspected sleep apnea. Sleep disorders go commonly undiagnosed and are associated with adverse pain experiences. While results do not support a synergistic effect of suspected insomnia and sleep apnea on pain, findings indicate that screening for sleep disorders is warranted and may have important implications for pain treatment.